2006
DOI: 10.1007/s00432-006-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of DDX1 and NAG gene amplification/overexpression to the prognosis of patients with MYCN-amplified neuroblastoma

Abstract: Our findings suggest that there may be a subset of NB in which enhanced DDX1 and low-NAG expression consequent to DDX1 co-amplification without NAG amplification contributes to susceptibility to intensive therapy. A larger study using an age cut-off of 18 months will be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…In agreement with reports published by two groups Kaneko et al, 2007), no significant difference was observed between patients presenting MYCN amplification, with or without DDX1 amplification, both for PFS and OS. Only one report suggested a better outcome for patients presenting DDX1 amplification in addition to MYCN amplification (Weber et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with reports published by two groups Kaneko et al, 2007), no significant difference was observed between patients presenting MYCN amplification, with or without DDX1 amplification, both for PFS and OS. Only one report suggested a better outcome for patients presenting DDX1 amplification in addition to MYCN amplification (Weber et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…2005; Kaneko et al, 2007). We could analyze the progression-free survival (PFS) and overall survival (OS) of a subset of patients presenting tumors with MYCN amplification, with (n 5 15) or without (n 5 21) DDX1 amplification.…”
Section: Relationship Between Amplicons and Patients Outcomementioning
confidence: 99%
“…For example, in one report high DDX1 expression in neuroblastoma was associated with better survival, 8 while a recent study showed that DDX1 expression was associated with improved local relapse-free-, distant metastasis-free-and overall survival in patients diagnosed with early-stage node-negative breast cancer, 9 suggesting a possible tumor suppressor role for DDX1. However, De Preter and colleagues found no evidence of any effect of DDX1 amplification on prognosis of patients with MYCH-amplified neuroblastomas, 10,11 while other reports suggested that the prognostic effect of DDX1 amplification/overexpression on MYCN is different between different subgroups, 12,13 providing a possible explanation for the different results obtained from the various studies. Although most reports indicate an oncogenic role for DDX1 in tumor development, much of the evidence is circumstantial rather than mechanistic.…”
Section: Ddx1mentioning
confidence: 50%
“…Besides MYCN, other genes such as DDXI [16] belonging to the family of genes encoding DEAD box proteins, ID2 (Inhibitor of DNA-binding/differentiation) [17], NAG (neuroblastoma amplified gene) [18], SNTG2, and TPO [19] have also been reported to be co-amplified in MYCN amplified neuroblastomas. A recent addition to this list is the ALK gene situated at 2p23.2.…”
Section: Discussionmentioning
confidence: 99%